Resinous deposits in Early Neolithic pottery vessels from the northeast of the Iberian Peninsula. (February 2023) - Breu, Adrià; Rosell-Melé, Antoni; Heron, Carl; Antolín, Ferran; Borrell, Ferran; Edo, Manel; Fontanals, Marta; Molist, Miquel; Moraleda, Núria; Oms, Francesc Xavier; Tornero, Carles; Vergès, Josep Maria; et al.
Highlights: Absence of compelling evidence regarding resin use amongst Early Neolithic populations in the Iberian Peninsula motivates this study. A combined approach using GC-FID, GC–MS and a score system assessing the presence of degraded diterpenoid compounds has been implemented. Analysis of 168 pottery vessels reveals the scarce but ubiquitous presence of degraded conifer resins in 10 Early Neolithic sites from the Northeast of the Iberian Peninsula. The contact between conifer resins and pottery suggests the existence of adhesive technologies specific to Early Neolithic societies. Abstract: The use of resinous substances, certainly one of the earliest technologies developed by humans, was well-known by Holocene hunter-gatherers at the onset of the Neolithisation process across Europe. Recent research has revealed the use of birch bark tar in the central Mediterranean far from this taxon's endemic regions both in the Paleolithic and Neolithic periods and shows that the first farmers from the Fertile Crescent hafted lithic tools and waterproofed artefacts using bitumen. The generalised absence of these natural products in south-western Europe may have thus forced a reformulation of Early Neolithic technologies by exploring and benefitting from existing knowledge in local European hunter-gatherer societies. However, information on resin use from the western Mediterranean is still scarce. Here, we report on the analysis of organic residues from 168 pottery sherds by gas chromatography and gas chromatography-mass spectrometry from 10 archaeological sites in this region dating from the second half of the VI th millennium to the first half of the V th millennium cal BC. In a limited number of samples, minor amounts of several diterpenoids diagnostic of aged Pinaceae resins were detected as mixtures with fats. The presence of pine in the palynological and carpological record supports the human exploitation of this taxon, but its minimal incidence in the anthracological record suggests that other species were selected as fuelwood. This supports the hypothesis that Pinaceae resins were used in association with pottery sporadically but ubiquitously either as its contents, or as post-firing treatments to waterproof the vessels. This demonstrates the development of adhesive technologies and resin-involved labour processes specific to Early Neolithic societies.